2022
DOI: 10.1111/poms.13607
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Encroachment, Information Sharing, and Channel Structure in Online Retail Platforms

Abstract: I n this study, we develop a game-theoretic model to study the encroachment and information sharing decisions in a supply chain with a manufacturer selling through an online retail platform. In the base model, the manufacturer decides whether to encroach or not by selling through an agency channel, in addition to an existing reselling channel, at the same platform, who decides whether or not to share information with the manufacturer. We fully characterize the equilibrium decisions and show how they depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(82 citation statements)
references
References 42 publications
1
81
0
Order By: Relevance
“…With the popularity of the platform's agency channel, few scholars begin to study whether suppliers should encroach through the platform's agency channel. For example, Ha et al (2022) investigate whether the supplier that cooperates with the platform in the reselling mode should enter through the platform's agency channel. They also analyze the platform's incentive to disclose information under different channel structures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the popularity of the platform's agency channel, few scholars begin to study whether suppliers should encroach through the platform's agency channel. For example, Ha et al (2022) investigate whether the supplier that cooperates with the platform in the reselling mode should enter through the platform's agency channel. They also analyze the platform's incentive to disclose information under different channel structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with the supplier, the retailer and the platform who are closer to end consumers can predict market demand from consumption data. In reality, many platforms cooperate with the supplier in information sharing (Ha et al, 2022; Niu et al, 2022; Zhang & Zhang, 2020). For instance, JD.com provides big data analysis reports to some suppliers to help them understand the market demand (Ebrun.com, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al (2021) study the impact of a supplier's capacity on his channel selection in a retail platform. Ha, Luo, and Shang (2022) study whether a manufacturer encroaches on the same platform through agency selling services in addition to a reselling channel and the platform's decision to share information. However, these studies do not consider the impact of multiple products on the supplier's channel selection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have identified that asymmetric information always creates benefits for the player who has the advantage of additional information, and it can adversely affect the supply chain profits and costs of the less informed party. Few studies consider the impact of information sharing on the channel structure of online retailing (Ha et al, 2021;. Therefore, it is important to address the impact of asymmetric information on e-tailer supply chains, which mainly depends on accurate information.…”
Section: Supply Chain Contracts With Information Asymmetry Issuesmentioning
confidence: 99%